Strategies to Overcome Pulse Production Constraints in West Bengal, India - Ray, M.; Ghosh, Pijush Kanti; Sengupta, Kajal (International Journal of Bio-resource and Stress Management, 2013)
Pulses are basic ingredient in the diet of a vast majority of Bengali population as they are perfect mix of high bio-logical value when supplemented with cereals. At present West Bengal is producing 1.58 lakh tons of pulses from 2.01 lakh ha area and the average productivity is 786 kg ha-1. But, the demand for pulses in the state is about 15.82 lakh tons. It means, the state has to produce 10 times its present production to meet the demand. In the last 15 years, area of pulses declined due to cropping system shift to vegetables and boro rice with introduction of irrigation facilities. Cultivation of pulses in marginal and sub-marginal and less fertile lands, non-availability of good quality seed, adoption of local low yielding varieties and problems in safe storage are the major constraints in pulse production. The mismatch between production and demand for pulses in the state can be narrowed down by following suitable agro-techniques, replacing non-descriptive local varieties with high yielding pest and disease resistant varieties, expanding it’s cultivation to non-conventional area with adequate transfer of technical knowledge, introducing it in the existing cropping systems, developing region specific high yielding cultivars, creating adequate and safe storage facilities